Coronavirus Disease 2019 Related Clinical Studies: A Cross-Sectional Analysis - Ma, Lin-Lu; Yin, Xuan; Li, Bing-Hui; Yang, Jia-Yu; Jin, Ying-Hui; Huang, Di; Deng, Tong; Wang, Yun-Yun; Ren, Xue-Qun; Ji, Jianguang; Zeng, Xian-Tao (Frontiers in Pharmacology, 2020)
Objective: The quality and rationality of many recently registered clinical studies related to coronavirus disease 2019 (COVID-19) needs to be assessed. Hence, this study aims to evaluate the current status of COVID-19 related registered clinical trial. Methods: We did an electronic search of COVID-19 related clinical studies registered between December 1, 2019 and February 21, 2020 (updated to May 28, 2020) from the ClinicalTrials.gov, and collected registration information, study details, recruitment status, characteristics of the subjects, and relevant information about the trial implementation process. Results: A total of 1706 studies were included 10.0% of which (n=171) were from France, 943 (55.3%) used an interventional design, and 600 (35.2%) used an observational design. Most of studies (73.6%) aimed to recruit fewer than 500 people. Interferon was the main prevention program, and antiviral drugs were the main treatment program. Hydroxychloroquine and chloroquine (230/943, 24.4%) were widely studied. Some registered clinical trials are incomplete in content, and 37.4% of the 1706 studies may have had insufficient sample size. Conclusion: The quality of COVID-19 related studies needs to be improved by strengthening the registration process and improving the quality of clinical study protocols so that these clinical studies can provide high-quality clinical evidence related to COVID-19.